Development and Pilot Implementation of the Genomic Risk Assessment for Cancer Implementation and Sustainment (GRACIAS) Intervention in Mexico. (2021) - Blazer, Kathleen R.; Chavarri-Guerra, Yanin; Villarreal Garza, Cynthia; Nehoray, Bita; Mohar, Alejandro; Daneri-Navarro, Adrian; del Toro, Azucena; Aguilar, Dione; Arteaga, Jazmin; Álvarez, Rosa Maria; Mejia, Rosa; Herzog, Josef; et al.
Abstract : PURPOSE: Genomic cancer risk assessment (GCRA) is standard-of-care practice that uses genomic tools to identify individuals with increased cancer risk, enabling screening for early detection and cancer prevention interventions. GCRA is not available in most of Mexico, where breast cancer (BC) is the leading cause of cancer death and ovarian cancer has a high mortality rate. METHODS: Guided by an implementation science framework, we piloted the Genomic Risk Assessment for Cancer Implementation and Sustainment (GRACIAS) intervention, combining GCRA training, practice support, and low-cost BRCA1 / 2 ( BRCA ) gene testing at four centers in Mexico. The RE-AIM model was adapted to evaluate GRACIAS intervention outcomes, including reach, the proportion of new patients meeting adapted National Comprehensive Cancer Network criteria who participated in GCRA. Barriers to GCRA were identified through roundtable sessions and semistructured interviews. RESULTS: Eleven clinicians were trained across four sites. Mean pre-post knowledge score increased from 60% to 67.2% (range 53%-86%). GCRA self-efficacy scores increased by 31% (95% CI, 6.47 to 55.54; P = .02). Participant feedback recommended Spanish content to improve learning. GRACIAS promoted reach at all sites: 77% in Universidad de Guadalajara, 86% in Instituto Nacional de Cancerología, 90% in Tecnológico de Monterrey, and 77% in Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán. Overall, a pathogenic BRCA variant was identified in 15.6% (195 of 1, 253) of patients. All trainees continue to provide GCRA and address barriers to care. CONCLUSION: We describe the first project to use implementation science methods to develop and deliver an innovative multicomponent implementation intervention, combining low-cost BRCA testing, comprehensive GCRA training, and practice support in Mexico. Scale-up of the GRACIAS intervention will promote risk-appropriate care, cancer prevention, and reduction in related mortality.